Antidepressant exposure in pregnancy and child sensorimotor and visuospatial development. (November 2021) - Galbally, Megan; Watson, Stuart J.; Spigset, Olav; Boyce, Philip; Oberlander, Tim F.; Lewis, Andrew J.
Abstract: Motor development underlies many aspects of education and learning. There has been uncertainty about the impact of exposure of antidepressant medication in pregnancy on child motor outcomes. This paper examines whether exposure to antidepressants in utero increases the risk of poorer motor development in two areas: sensorimotor and visuospatial processing. Data were obtained from 195 women and children across 3 groups: women with untreated depression in pregnancy, women treated with antidepressants and control women. Data were collected across pregnancy, postpartum and until 4 years for mother and child. Maternal depression was established at baseline with the Structured Clinical Interview for DSM-IV. Antidepressant exposure, including type, dose and timing, was measured through repeated self-report across pregnancy and the postpartum, medical records at delivery and in cord blood samples collected at delivery. Child sensorimotor and visuospatial outcomes were assessed at 4 years of age with four subtests from the NEPSY-II. Our study found for sensorimotor development, visuomotor precision completion time was associated with better performance for antidepressant-exposed children compared to those with mothers with untreated depression. Yet another measure of sensorimotor development, motor manual sequences, was poorer in those exposed to antidepressants. One subtest for visuospatial processing, block construction, was associated with poorer performance in antidepressant-exposed children who had poor neonatal adaptation and those exposed to a higher dose of antidepressant. These findings suggest an inconsistent association between sensorimotor development and antidepressant use in pregnancy. However, the findings for visuospatial processing would support further exploration of antidepressant associated poor neonatal adaption and later motor development.